2023
DOI: 10.1002/arch.21989
|View full text |Cite
|
Sign up to set email alerts
|

A novel GSTe2 involved in metamorphosis by regulating 20E signal pathway in Tribolium castaneum

Abstract: Insect‐specific epsilon glutathion S‐transferases (GSTs) are a class of multifunctional GST superfamily, which play important roles in detoxification of xenobiotic substances. Most research on GSTs has focused on insecticide detoxification and resistance, with little research on other physiological functions. Here, we identified and cloned the novel GSTe2 from Tribolium castaneum (TcGSTe2). Recombinant TcGSTe2 protein was successfully overexpressed in Escherichia coli and purified with affinity purification, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Moreover, TcGclc knockdown showed metamorphosis deficiency, downregulation of 20E‐related genes and partial rescue of the deficiency phenotype by exogenous 20E injection (Figs 3 and 4), which suggested that TcGclc knockdown led to metamorphosis deficiency by inhibition of 20E signal pathways. Previous studies have shown that GSH‐based GSTs were involved in metamorphosis by upregulating the 20E signal pathway in T. castaneum , 18 D. melanogaster , 32 Bombyx mori 33 and Aedes aegypti 34 ; in particular, the insect ecdysteroidogenic GST Noppera‐bo, which is the only known GST essential for ecdysone production in dipterans and lepidopterans 32,33 . Moreover, the Gclc null mutant in Drosophila indicated that Gclc‐mediated GSH biosynthesis is coupled to Noppera‐bo‐dependent ecdysone biosynthesis 16 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, TcGclc knockdown showed metamorphosis deficiency, downregulation of 20E‐related genes and partial rescue of the deficiency phenotype by exogenous 20E injection (Figs 3 and 4), which suggested that TcGclc knockdown led to metamorphosis deficiency by inhibition of 20E signal pathways. Previous studies have shown that GSH‐based GSTs were involved in metamorphosis by upregulating the 20E signal pathway in T. castaneum , 18 D. melanogaster , 32 Bombyx mori 33 and Aedes aegypti 34 ; in particular, the insect ecdysteroidogenic GST Noppera‐bo, which is the only known GST essential for ecdysone production in dipterans and lepidopterans 32,33 . Moreover, the Gclc null mutant in Drosophila indicated that Gclc‐mediated GSH biosynthesis is coupled to Noppera‐bo‐dependent ecdysone biosynthesis 16 .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Moreover, the Gclc null mutant in Drosophila indicated that Gclc-mediated GSH biosynthesis is coupled to Noppera-bo-dependent ecdysone biosynthesis. 16 In coleopteran insects such as T. castaneum, Nopperabo is not conserved 32 ; however, some GSTs also are involved in metamorphosis, 17,18 implying that Gclc-mediated GSH biosynthesis may be coupled to another type of GST for ecdysone biosynthesis. In terms of this, the current results suggest that TcGclc may participate in metamorphosis by providing GSH for GSTs that are involved in 20E signal pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main strategy for pest control is the use of synthetic insecticides, however, which develop rapid insecticide resistance, resulting in increased use of insecticides, negative health risks, and environmental pollution. , A family of phase II detoxification enzymes, glutathione S -transferases (GSTs) play a crucial role in the cellular detoxification of xenobiotics . Previous studies revealed that some TcGSTs (TcGSTd1–3, TcGSTs6, TcGSTe2) required GSH for development and detoxification in T. castaneum, suggesting the possibility that GSH biosynthesis could be a potential target for pest control.…”
Section: Introductionmentioning
confidence: 99%